Effects of defaunator combined with microbial growth factors on ruminal digestibility ofrice - Amlius Thalib; D Devi; Y Widiawati; Z.A Mas’ud (Indonesian Center for Animal Research and Development (ICARD), 1998)
A system of defaunating agent combined with microbial growth factors (FPM) was conducted to improve the ruminal digestion of rice straw. Combination of methanol-extracted Sapindus rarak fruit (EKM) with each FPM was added into anaerobic medium of ruminal fermentation. Rice straw was used as substrate and inoculum used was rumen fluid of sheep. Fermentation microbial of the substrate was incubated at 39°C for 96 hours. The experiment consisted of 10 treatments: control without EKM; control + EKM (1 .000 ppm); control +EKM combined with Zn (8 ppm), Cu (0 .8 ppm), folic acid (0.1 ppm), thiaminhydrochloride (0 .05 ppm), riboflavin (0.05 ppm), phenylpropionic acid (100 ppm), molasses (45 ppin), and mixture of all FPM used (Mix FPM). Measurements were: gas production; protozoal and bacterial populations; contents of volatile fatty acids (VFA), lactic acid andNH3N; pH ofmedium. The results show that FPM increase EKM effects on rwninal digestibility of rice straw except treatments of thiaminhydrocloride and riboflavin. The highest cumulative gas production was obtained by treatment of EKM combined with Mix FPM (168 ml versus 91 nrl of treatment of EKM with out FPM). EKM individually or combined with FPM could eliminate 46-83% protozoal population, where the highest elimination of protozoal population was given by combination of EKM with Mix FPM(83%): Elimination of protozoal population caused increment of bacterial population on all treatments except on folic acid treatment. The highest increment ofbacterial population was given by treatment of combination EKMwith Mix FPM (>500%). Therefore combination of EKMwith Mix FPM is concluded to be the most effective in improving ruminal digestibility of rice straw. Key words : Defaunating agent, microbial growth factors, rruninal digestion